Transcriptional regulation during Drosophila spermatogenesis - Lim, Cindy (Landes Bioscience, 2012)
Drosophila spermatogenesis has become a paradigmatic system for the study of mechanisms that regulate adult stem cell maintenance, proliferation and differentiation. The dramatic cellular differentiation process from germline stem cell (GSC) to mature sperm is accompanied by dynamic changes in gene expression, which are regulated at transcriptional, post-transcriptional (including translational) and post-translational levels. Post-transcriptional regulation has been proposed as a unique feature of germ cells. However, recent studies have provided new insights into transcriptional regulation during Drosophila spermatogenesis. Both signaling pathways and epigenetic mechanisms act to orchestrate the transcriptional regulation of distinct genes at different germ cell differentiation stages. Many of the regulatory pathways that control male gamete differentiation in Drosophila are conserved in mammals. Therefore, studies using Drosophila spermatogenesis will provide insight into the molecular mechanisms that regulate mammalian germ cell differentiation pathways.